VD_FINDINFO Arrêt / 2012 / 66 vom 9. November 2000 - VD Tribunal cantonal (2000)
DROIT D'ÊTRE ENTENDU, ADMISSION DE LA DEMANDE, SUPPRESSIONEN GÉNÉRAL, TUTELLE | 420 al. 2 CC, 438 CC, 29 al. 2 Cst., 91 al. 2 LVCC